Berdasarkan PENGATURAN INVESTASI UNTUK MEWUJUDKAN KESEJAHTERAAN MASYARAKAT TEMPATAN AKIBAT DAMPAK PENGEBORAN MINYAK BLOK ROKAN (RIAU, ROKAN HILIR): PENGATURAN INVESTASI UNTUK MEWUJUDKAN KESEJAHTERAAN MASYARAKAT TEMPATAN AKIBAT DAMPAK PENGEBORAN MINYAK BLOK ROKAN (RIAU, ROKAN HILIR) - Adinda, Fadhel (Jurnal Kajian Ilmu Hukum, 2022)
Based on the mandate of the preamble of the 1945 Constitution in the fourth paragraph, the state is obliged to seek to improve the welfare of the Indonesian people. Investment is one way to improve the welfare of the Indonesian people. Investment does not only benefit investors who have capital, but also has an impact on the community around the place where the investor's business field is carried out. However, all of this will be carried out properly if the regulation regarding investment already includes the wishes and needs of today's society, because in its development the law must be dynamic in order to obtain the initial goal of increasing the welfare of the people's lives. This research uses normative legal research methods, sourced from laws and regulations, books, journals and everything that supports this research.